Sensing soluble uric acid by Naip1-Nlrp3 platform - Tárcio Teodoro Braga; Mariana Rodrigues Davanso; Davi Mendes; Tiago Antônio de Souza; Anderson F. Brito; Mário Costa Cruz; Meire Ioshie Hiyane; Dhêmerson Souza de Lima; Vinícius Nunes Cordeiro Leal; Juliana de Fátima Giarola; Dênio Emanuel Pires Souto; Tomasz Próchnicki; et al. (2020)
Summary The immune system can recognize microbes and sterile tissue damage. Among the damage-associated molecular patterns (DAMPs), uric acid is considered a major component which can trigger inflammation. It represents a breakpoint in the evolutionary history of humans as our ancestors lost the uricase gene, the enzyme responsible for its cleavage. High soluble uric acid (sUA) concentration is able to increase IL-1β in murine, but not human macrophages. We observed that sUA increased the mRNA expression of Naip1 in murine macrophages, and, therefore, we hypothesized that the recognition of sUA can be made by a Naip1-Nlrp3 inflammasome platform. Additionally, we used genome-wide transcriptome analysis, functional analyses and structural modeling predictions and observed that virus-transduction of murine Naip1 into human macrophages induced IL-1β after sUA stimulus, besides leading to fatty acid production and an inflammation-related response. Moreover, pharmacologic inhibition and genetic loss of Nlrp3 led to decreased IL-1β production upon sUA stimulus. Surface plasmon resonance and quartz crystal microbalance showed that sUA is able to interact with Naip1. Naip could be a lost receptor for sUA in the evolutionary process and a better understanding of the immune modulatory function of sUA could lead to design rational novel anti-hyperuricemic therapies.